Conceptual Study Of Enzymatic Sugar Ester Synthesis In The PBR At Steady-State And Isothermal Conditions - Mohamed Firaz, Mohamed Zarif Wazif (Universiti Sains Malaysia, 2021)
Lipase was used widely in the production of sugar ester especially in food processing which used PBR as the reactor. The amount of yield produce is affected by the enzymatic activity which also effected by binding energy, temperature and amount of concentration of the substrate used. Ideal parameters based on experimental and also simulation path are the major problem in order to produce higher amount of sugar esters. The equation used for simulation were obtained based on the design equation for PBR and based on the two substrate reaction (Varde & Fogler, 2001). Two parameters were compared to obtain an optimum yield of sugar ester which are the temperature and the molar ratio of substrate. This parameters are validate and compared between the results obtained from Sebatini experiment in the literature with the simulation by using POLYMATH. From the comparison, Simulation result are much more accurate based on the validation of R2 methods as it can improve the data that used by the experimental. In agreement with Harwell and Co-workers, The result that obtained by the experimental can be modify by using the simulation methods (Harwell et al., 2017). The trend of the graph for the effect of temperature against yield of sugar ester shows the similar shape which the yield obtained was the highest at 40⁰C but slightly different for the effect of substrate concentration molar ratio against yield of sugar ester as the as it stated that the molar ratio of sugar: fatty acid for simulation should be 1:1 while for the experimental was 1:2 respectively. After obtaining the optimum and ideal parameters and constant for the sugar ester based on the comparison of both sources, the effect of kinetic parameter and thermodynamic parameter were discussed. From what obtained in kinetic parameter, the higher activation energy of substrate bind to enzyme and the lower the inhibition activation energy will increase rate of reaction. While for the thermodynamic parameters, the higher the activation energy of catalysis process, △Gcat, activation energy during equilibrium, △Heq and equilibrium temperature, Teq and the lower the activation energy of thermal inactivation process, △Ginact, will yield lower rate of reaction. This shows that the enzyme can act ideally if the activation energy of substrate binding higher while the inhibition activation energy is lower. Beside that, enzyme also can act ideally if the activation energy of catalysis, activation energy during equilibrium, and equilibrium temperature are lower while if the activation energy of thermal inactivation process is higher.